The ethics of nurturing children in traditional Malay literature - Hamdan, Rahimah (Serials Publications, 2017)
This paper was aimed at identifying 'the ethics of nurturing of children' in the Adab Literature of Tajus Salatin and comparing these elements with the works in the Malay Hikayat genre. This study was carried out in response to allegations by Western scholars, who have little regard for the 'literary' worth of Malay Literature, especially in the genre of Malay Hikayat. In their opinion, the authors of this genre could not differentiate between science and fiction, facts and illusion, and even went to the extent of entertaining with illustrations of supernatural elements that were illusory and did not benefit their audience in any way. Accordingly, by carrying out a textual analysis of Tajus Salatin and several selected works from the genre of Malay Hikayat, this paper highlighted the adab (ethics) of 'nurturing children', which has been an important responsibility of all individuals who are parents to 'offspring' entrusted to them by Allah s.w.t. since the traditional era. It was concluded in this study that the Malay authors successfully carried out their responsibilities with literary awareness because all the items in Chapter 14 of Tajus Salatin were discovered in the Malay Hikayat, which were often doubted as to their seriousness and factual accuracy. Evidently, the Malay Hikayat were not only entertaining, with their descriptions of illusory supernatural elements, but were also loaded with important guidelines for the Malay audience. This indirectly proved that the Malay authors, who were rich in wisdom, produced 'literature that reflected the national culture'.